2011
DOI: 10.1016/j.resp.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the vagal feedback on cardiorespiratory coupling in anesthetized rats

Abstract: Cardiorespiratory coupling can be significantly influenced by both pontine and vagal modulation of medullary motor and premotor areas. We investigated influences of the pontine intertrigeminal region (ITR) and peripheral vagal pathways on the coupling between systolic blood pressure (SBP) and respiration in 9 anesthetized rats. Glutamate injection into the ITR perturbed both respiration and SBP and decreased SBP-respiratory coherence (0.95±0.01 vs 0.89±0.02; (p=0.01). Intravenous infusion of serotonin (5-HT) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The study proposed that if stimulation of the vagus nerve were to be repeated, before the last inhibition response ended then sustained inhibition may be maintained (Zagon and Kemeny 2000). Animal studies have shown cardiorespiratory coupling ceases after bilateral vagotomy, suggesting that cardiorespiratory synchronization is mediated by the vagus nerve, which imparts parasympathetic control (Campbell and Egginton 2007;Dick et al 2009;Topchiy et al 2011). In addition, schizophrenic patients exhibit decreased levels of cardiorespiratory synchronization, which indicates decreased vagal modulation and inhibition in the brainstem (Peupelmann et al 2009).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 99%
“…The study proposed that if stimulation of the vagus nerve were to be repeated, before the last inhibition response ended then sustained inhibition may be maintained (Zagon and Kemeny 2000). Animal studies have shown cardiorespiratory coupling ceases after bilateral vagotomy, suggesting that cardiorespiratory synchronization is mediated by the vagus nerve, which imparts parasympathetic control (Campbell and Egginton 2007;Dick et al 2009;Topchiy et al 2011). In addition, schizophrenic patients exhibit decreased levels of cardiorespiratory synchronization, which indicates decreased vagal modulation and inhibition in the brainstem (Peupelmann et al 2009).…”
Section: Possible Role Of Membrane Potential In Cardiorespiratory Modmentioning
confidence: 99%